PENGARUH PENGEMBANGAN KARIR STRATEGI REKRUTMEN SELEKSI DAN TERHADAP KINERJA KARYAWAN PADA PT. X - Ruben Christopher; Ian Nurpatria Suryawan (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
This research aims to find out the influence of career development, recruitment strategies and selection on employee performance at PT. X. This research design uses quantitative descriptive, using a likert scale divided into five points, as well as secondary data in the form of information obtained from internal companies. Purposive sampling methods with primary and secondary data are used in sample determination. The sample used 119 respondents and data analysis using a double linear regression with IBM SPSS statistic 25 as a test tool. The results of this study show that there is an influence of career development, recruitment strategies and selection on employee performance in PT. X.